2011
DOI: 10.4028/www.scientific.net/amm.52-54.881
|View full text |Cite
|
Sign up to set email alerts
|

Engraving and Milling Machine Design Based on Open CNC System

Abstract: In view of application requirements, control axes, the development cycle and other factors of open CNC machine tools, we consider the modular as the guiding ideology and propose a design method of three-dimensional engraving and milling machine based on open CNC system. In this paper we make a detailed design for mechanism structure and control system. Experiments show that this machine has milling and engraving capabilities, can process metal and non-metallic parts, which is a high efficiency, multi-function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The CNC engraving milling (CNC-EMM) process has also been used by some researchers for various purposes [13][14][15][16][17]. An open-architecture numerical control of motion and PLC for CNC-EMM was proposed by Lian et al [13] to achieve high performance at high speed with greater precision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNC engraving milling (CNC-EMM) process has also been used by some researchers for various purposes [13][14][15][16][17]. An open-architecture numerical control of motion and PLC for CNC-EMM was proposed by Lian et al [13] to achieve high performance at high speed with greater precision.…”
Section: Introductionmentioning
confidence: 99%
“…An open-architecture numerical control of motion and PLC for CNC-EMM was proposed by Lian et al [13] to achieve high performance at high speed with greater precision. In another important work, a design strategy was made to develop a three-dimensional open-system-based CNC engraving milling machine for manufacturing parts from metallic and non-metallic materials [14]. The experiments showed that the developed machine could produce parts of superior quality with a high degree of efficiency.…”
Section: Introductionmentioning
confidence: 99%